Using Piezosurgery in Anterior Cervical Discectomy and Fusion to Treat Complex Cervical Spondylotic Myelopathy Is Safe and Effective - Yu-Wei Li; Hao-Jie Chen; Shi-Xin Zhao; Xiu-Zhi Li; Hai-Jiao Wang; Peng Zhou; Wei Cui; Wei Xiao; Fan Li; Bingtao Hu (Advances in Orthopedics)
Objective. To investigate the safety and efficacy of piezosurgery in anterior cervical discectomy and fusion (ACDF) for cervical spondylotic myelopathy (CSM). Methods. 47 patients with complex CSM (cCSM) underwent ACDF surgery from 2014 to 2017. Among these patients, 26 underwent ACDF using piezosurgery (group A) and 21 underwent ACDF by using traditional tools such as high-speed air drill, bone curette, and Kerrison bone punch (group B). Average surgical time, intraoperative blood loss, surgical complications, preoperative and postoperative Japanese Orthopaedic Association (JOA) scores, and improvement rate were measured. Results. Average surgical time and intraoperative blood loss were significantly lower in group A than those in group B (P<0.01). The incidences of surgical complications were 3.8% and 23.8% in the A and B groups (P<0.05), respectively. There were no significant differences in JOA scores and improvement rates between data collection periods at preoperative, 3-day postoperative, and 1-year postoperative follow-ups (P>0.05). Conclusion. For treating cCSM, both the piezosurgery and traditional tools led to significant neurological improvement. However, the piezosurgery was superior to the traditional tools in terms of surgical time, blood loss, and complication rate. Hence, piezosurgery was a safe and effective adjunct for ACDF treating cCSM.